Comparison of transcerebellar diameter with conventional fetal biometric parameters like biparietal diameter, head circumference, femur length and abdominal circumference in predicting gestational age in third trimester - Dewangan, Bhagyashree; Agarwal, Shivani; Mendiratta, Suman Lata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Gestational age estimation in third trimester is very crucial to impart holistic antenatal care and a pre-requisite to plan various interventions. Transcerebellar diameter can predict gestational age reliably as it grows progressively with gestation and is not affected by fetal lie, skull shape and fetal growth disorders. This study was performed to compare TCD with conventional parameters like BPD, HC, FL and AC in accurate prediction of gestation age. Methods: Fetal biometry was performed on 140 women with singleton pregnancy by abdominal ultrasound. Women included were sure of their LMP, had dating scan and fetal anomalies were ruled out. Analysis was done using Pearsons coefficient (r) and regression, p<0.05 was considered statistically significant. Results: GA by LMP showed maximum correlation with GA by TCD (r=0.920 p<0.001) followed by HC (r=0.871) and AC (r=0.833). Least correlation was seen with BPD (r=0.789). On comparing GA by TCD and GA by conventional parameters, TCD correlated maximally with HC (r=0.882) followed by FL (r=0.868) and BPD (r=0.853) and least correlation was seen with AC (r=0.793). Conclusions: TCD can serve as a reliable parameter for evaluation of GA in women whose LMP is unknown or when they present late in pregnancy without having a dating scan because of strong and significant correlation of GA by TCD. Moreover, TCD can also provide accurate GA in cases of fetal growth restriction, macrosomia, skeletal dysplasia where BPD, AC, FL becomes unreliable. Therefore, it should be included in routine fetal biometry.